TEKS RANDAI UMBUIK MUDO KARYA MUSRA DAHRIZAL - Suria Dharma Eka Sakti (Universitas Andalas, 2010)
This research describes the shaman practice in Umbuik Mudo randai script. This research use structure and anthropological theory. Structure analysis show that main character, Umbuik Mudo, use this practice to regain his pride. Furthermore, the object show the importance of characters status (rich and poor), pride, and behavior ethics,